Meta-analyses and systematic reviews on myocardial revascularization: comparing survival, myocardial infarction, repeated revascularization and angina symptom reduction rates - I. V. Samorodskaya (Кардиоваскулярная терапия и профилактика)
The review summarizes data of meta-analyses and systematic reviews on comparative myocardial revascularization results. The review has been performed according to Cochrane Review Database method, without quantitative data pooling into one meta-analysis. Coronary artery bypass grafting (CABG) surgery is more effective than pharmaceutical treatment (PHT) in improving survival, but not in preventing myocardial infarction (MI) among some patients. CABG is more effective than endovascular myocardial revascularization in prevention of repeated revascularization, but not in improving quality of life (with diabetic patients as an exception). Coronary artery stenting is more effective than transluminal balloon angioplasty in reducing recurrent revascularization rates, but not in increasing life expectancy or preventing MI (similar results obtained for coated an non-coated stents). Clinical practice use of randomized trial and meta-analysis results is restricted by rapid development of medical technologies.